Roles of FoxM1‐driven basal β‐cell proliferation in maintenance of β‐cell mass and glucose tolerance during adulthood. Issue 10 (15th July 2022) - Kohata, Masato; Imai, Junta; Izumi, Tomohito; Yamamoto, Junpei; Kawana, Yohei; Endo, Akira; Sugawara, Hiroto; Seike, Junro; Kubo, Haremaru; Komamura, Hiroshi; Sato, Toshihiro; Hosaka, Shinichiro; et al.
ABSTRACT: Aims/Introduction: Whether basal β‐cell proliferation during adulthood is involved in maintaining sufficient β‐cell mass, and if so, the molecular mechanism(s) underlying basal β‐cell proliferation remain unclear. FoxM1 is a critical transcription factor which is known to play roles in 'adaptive' β‐cell proliferation, which facilitates rapid increases in β‐cell mass in response to increased insulin demands. Therefore, herein we focused on the roles of β‐cell FoxM1 in 'basal' β‐cell proliferation under normal conditions and in the maintenance of sufficient β‐cell mass as well as glucose homeostasis during adulthood. Materials and Methods: FoxM1 deficiency was induced specifically in β‐cells of 8‐week‐old mice, followed by analyzing its short‐ (2 weeks) and long‐ (10 months) term effects on β‐cell proliferation, β‐cell mass, and glucose tolerance. Results: FoxM1 deficiency suppressed β‐cell proliferation at both ages, indicating critical roles of FoxM1 in basal β‐cell proliferation throughout adulthood. While short‐term FoxM1 deficiency affected neither β‐cell mass nor glucose tolerance, long‐term FoxM1 deficiency suppressed β‐cell mass increases with impaired insulin secretion, thereby worsening glucose tolerance. In contrast, the insulin secretory function was not impaired in islets isolated from mice subjected to long‐term β‐cell FoxM1 deficiency. Therefore, β‐cell mass reduction is the primary cause of impaired insulin secretion and deterioration of glucose tolerance due to long‐term β‐cell FoxM1 deficiency. Conclusions: Basal low‐level proliferation of β‐cells during adulthood is important for maintaining sufficient β‐cell mass and good glucose tolerance and β‐cell FoxM1 underlies this mechanism. Preserving β‐cell FoxM1 activity may prevent the impairment of glucose tolerance with advancing age. Abstract : β‐cell FoxM1 plays a critical role in basal, low‐level β‐cell proliferation throughout adult periods from youth to middle age. Long‐term FoxM1 deficiency suppresses β‐cell mass increases with advancing age, and impaired insulin secretion. Inhibition of FoxM1‐driven basal β‐cell proliferation worsen glucose tolerance, indicating inability to maintain sufficient β‐cell mass.